Interplay of clinical biomarkers in allergic asthma diagnosis and severity: A case-control study: Biomarkers in AA diagnosis and severity - Khaleel Mohammed, Zainab; Wasman Smail, Shukur; Janson, Christer; Amin, Kawa (Cellular and Molecular Biology, 2024)
Given asthma’s large phenotypic diversity, the study was aimed to use specific biomarkers to characterize Allergic asthma (AA) and its severity. Blood was collected from 42 healthy controls (HCs) and 96 patients with AA. Biomarkers related to blood cell number and function: total leukocyte count (TLCs), neutrophil, lymphocyte, monocyte, eosinophil, basophil, neutrophil-to-lymphocyte ratio (NLR), immunoglobulin E (IgE), tryptase and eosinophilic cationic protein (ECP) as well as remodelling biomarkers (Matrix metalloproteinase (MMP-9), (MMP-16), Fibroblast growth factor (FGF-18) and (FGF-23) and alpha-skeletal muscle actin-1 (ACTa-1) were measured. Significant differences were observed in hematological parameters with higher levels of total leukocytes, eosinophil, and basophil counts in the AA group compared to HCs. The disease group also had significantly higher levels of several serum biomarkers (IgE, TPs, ECP, MMP-9, MMP-16, FGF-18, FGF-23, and ACTa-1) compared to HC. Forced expiratory volume 1 (FEV1) and forced vital capacity (FVC) had a strong negative correlation with ECP, IgE, and ACTa-1. FEV1 was negatively correlated with MMP-16 and tryptase. Patients with AA have higher levels of several biomarkers, such as MMP-9, MMP-16, FGF-18, FGF-23, IgE, tryptase, and ACTa-1. In addition, IgE, tryptase, ACTa-1, and MMP-16 are related to lung function impairment in AA. This indicates that measuring multiple biomarkers may be of value in the future when diagnosing and monitoring AA.